2017
DOI: 10.1051/matecconf/201710102019
|View full text |Cite
|
Sign up to set email alerts
|

Bio-coal briquettes made from South Sumatera low rank coal and palm shell charcoal for using in small industries

Abstract: The objective of this study is to blend the South Sumatera low rank coal and palm shell charcoal for producing bio-coal briquettes which have better fuel properties. The experimental study for making biocoal briquettes was carried out to examine the effect of raw material composition and binder type on the quality of the briquettes produced. A screw conveyor machine equipped with a three blade stirred and designed with the length of 40 cm, mixing process diameter of 10 cm and the capacity of 2 kg bio-coal briq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…In this work, the briquette sample produced from palm shells was found to have higher calorific value than briquettes from corncob and soybean stem. Previous researcher reported that the mixture of low rank coal and palm shell resulted 6438 kcal/kg (Sipatuhar et al, 2018), which is lower compared to this finding.…”
Section: Calorific Value/heating Valuecontrasting
confidence: 59%
“…In this work, the briquette sample produced from palm shells was found to have higher calorific value than briquettes from corncob and soybean stem. Previous researcher reported that the mixture of low rank coal and palm shell resulted 6438 kcal/kg (Sipatuhar et al, 2018), which is lower compared to this finding.…”
Section: Calorific Value/heating Valuecontrasting
confidence: 59%
“…Among these tehniques, binder utilization is more accessible for people especially the most vulnerable and poorest. However, in some cases, the binder is derived from food (Koteswararao et al, 2016;Sipahutar et al, 2017). This poses a number of problems as it is always the case when we use crop production or agricultural lands to produce energy (bioenergy).To avoid as much as possible these difficulties, we test clay as binder.…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…Several researchers have carried out ash analyses using various techniques for different fuel samples. Most researchers analysed mainly for the percentage content of ash in fuel using conventional ash content test specified by ASTM D3174 standard 3 , 15 , 19 , 20 . To properly elucidate the role of the ash content of fuel during the application, a more detailed analysis is required.…”
Section: Introductionmentioning
confidence: 99%
“…However, these biomasses have been reported to have ash compositions that may weaken its usefulness for energy generation. Hence, the need to use biomass as a partial replacement for fossil fuel (coal) in energy generation 11,[13][14][15] . The ash content describes the product of incomplete combustion, which may be majorly minerals but could still contain some amount of organic or other oxidizable residues 16 .…”
mentioning
confidence: 99%